2020
DOI: 10.1519/jsc.0000000000003890
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease-19 Quarantine Is More Detrimental Than Traditional Off-Season on Physical Conditioning of Professional Soccer Players

Abstract: Grazioli, R, Loturco, I, Baroni, BM, Oliveira, GS, Saciura, V, Vanoni, E, Dias, R, Veeck, F, Pinto, RS, and Cadore, EL. Coronavirus disease-19 quarantine is more detrimental than traditional off-season on physical conditioning of professional soccer players. J Strength Cond Res 34(12): 3316–3320, 2020—Beyond the severe health crisis, the coronavirus disease 2019 has also affected the high-performance sports scenario. In soccer, practitioners are concerned about the effects of long-term detraining on players' c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
113
5
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(142 citation statements)
references
References 8 publications
9
113
5
15
Order By: Relevance
“…In Brazilian soccer players, over normal off-season, 63 days of quarantine affected several physical performance tests (22).…”
Section: Resultsmentioning
confidence: 99%
“…In Brazilian soccer players, over normal off-season, 63 days of quarantine affected several physical performance tests (22).…”
Section: Resultsmentioning
confidence: 99%
“…As expected with team practice limited by COVID-19, in which the lack of training with matchintensity and timing in the football specific actions may have influenced these game variables. Another study showed that this quarantine was more detrimental to football players' physical conditioning than off-season, which may affect the performance variables during the games (Grazioli et al 2020). An interesting result was the higher passes accuracy after SD than before.…”
Section: Discussionmentioning
confidence: 99%
“…In football, the 2019/2020 season for almost all leagues was initially postponed indefinitely, or cancelled, due to COVID-19 pandemic, until league decision for a safety comeback. Discussion about the effects of prolonged quarantine on football players' performance has been a critical point debated in the literature (Grazioli et al 2020). During the quarantine period, studies have suggested general home training for football (Azevedo et al 2020) or guidelines for return to fitness training, physical preparation and recovery during these conditions (Mohr et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations